THE EFFECTIVENESS OF MIND MAPPING-SILENT CARD SHUFFLE - Rahmawati, Puspa Merah; ., Indrawati; Fitriati, Sri Wuli (ELT Forum: Journal of English Language Teaching, 2017)
This paper is based on the quasi-experimental research which aims to find out the effectiveness of mind mapping-silent card shuffle combination to improve studentsâ€™ achievement in narrative writing skill. The subject of this study was the eighth grade students of a state junior high school in Semarang in the academic year of 2015/2016. The sample consisted of 64 students from two classes. The data were derived from test, interview, and documentation. The data were then measured and analyzed by the statistical and interpretation. The result showed that after the students were given treatment by using mind mapping-silent card shuffle combination,the mean scores of the experimental group increased about 28.49%. The t-test showed that tvalue (3.839) was higher than ttable (1.998). It can be concluded that the working hypothesis (Ha) which states that â€œThere is a significant difference of effectiveness and learning achievement in writing narrative story of students who are taught by using mind mapping-silent card shuffle combination technique and those who are not taught by using that techniqueâ€ is accepted. Therefore, a mind mapping-silent card shuffle combination technique is effective for students to improve their achievement in narrative writing skill.